ANALISIS PENYEBAB KETIDAKLENGKAPAN PENGISIAN GENERAL CONSENT DI TPP RAWAT JALAN : STUDI KASUS DI RUMAH SAKIT UNIVERSITAS - Oktavia Ariyanti, Rizka (Jurnal Administrasi Publik, 2024)
The cause of incompleteness filling out of general consent in outpatient admission: a case study in university hospital. According to Indonesian Laws, hospital is required to maintain medical records. One important indicator in medical records is completeness filling out general consent. All patients who come to the hospital required to register at outpatient admission, which is under medical records department. One of activities that must be carried out by outpatient admission officer is filling out general consent. This study is conducted in university hospital with 193 beds. In this hospital, the compliance of filling out outpatient general consent is 29% from the standard of 80%. The aim of this study is to analyze the cause of incompleteness filling out outpatient general consent. Determination the root of the problem was done by using fishbone diagram and 5 Whys methods and determination of the alternative solution was done by using CARL. The result found that admission officer compliance was the most contributing factor of incompleteness filling out outpatient general consent.